Al Ahkaam al mabniyyah Ala Al-jam'i Baina al-Adillah Min kitab al-Buyu' ila Kitab al-jami' fi Kitab Subulis Salam lis Shan'ani=الأحكام المبنية على الجمع بين الأدلة من كتاب البيوع إلى كتاب الجامع في كتاب سبل السلام للصنعاني - Masmu', Khoirul, Dr. M. Muinudinillah Basri, M.A, Dr. Imron Rosyadi M.Ag (2015)
This research is intended to understand the problems of fiqh with contradictive hadiths, seeking out debatable issues, and to solve those issues with various methods in combining the contradictive hadiths so that it will not be debatable. The methods used in combining the meanings of the contradictive hadiths are al-jam'u bi at-takhsis, al-jam'u bit-taqyid, al-jam'u bihamlil amri al an-nadb, al-jam'u bihamlin nahyi al al-karahah, al-jam'u bi hamli al-lafzhi al-majaz, a-jam'I bi ikhtilafil haal, al-jam'u bil akhzhii bi az-ziyadah, and al-jam'u bi jazawil amraini 'ala jawaz. On 'Subulus Salam', from 'kitab al buyu' until 'kitab al-jami', there are 51 problems that is based on contradictive hadith. In This research, it is explained about the contradictive issues and how to combine them. Ash shanani when answering the contradictive hadith is follow the opinion from the majority of moslem cleric which is prioritizing 'al-jam'u bainal adillah' while it is still possible to use. This prioritizing is based on the principle that said taking both of hadith is better than taking only one hadith and abandoning the others.